PENGARUH ROLE CONFLICT, ROLE AMBIGUITY, SELF-EFFICACY, SENSITIVITAS ETIKA PROFESI TERHADAP KINERJA AUDITOR DENGAN EMOTIONAL QUOTIENT SEBAGAI VARIABEL MODERATING (Studi Empiris pada Kantor Akuntan Publik di Pekanbaru, Batam, dan Medan) - Ulfa Afifah; Ria Nelly Sari; Meilda Wiguna (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2015)
This study examines the influence of role conflict, role ambiguity, self-efficacy, sensitivity of professional ethics to auditor performance with emotional quotient as Moderating variable. Respondents in this study are auditors who worked for public accounting firm in Pekanbaru, Batam, Medan. The number of auditor that were visited in this study were 145 auditors from 29 public accounting firms. The method of determining the sample is by using purposive sampling method, while the data processing methods used by researcher are the multiple regression and moderate regression analysis. The result shows that the role conflict, role ambiguity, negatively and significantly influence auditor performance. Self-efficacy and sensitivity of professional ethic positively and significantly influence auditor performance. Emotional quotient can be a moderating variable to role conflict, self-efficacy, sensitivity of professional ethics, but it cannot be a moderating variable for role ambiguity.Keywords: role conflict, role ambiguity, self-efficacy, sensitivity of professional ethics, emotional quotient, auditor performance